Identification and evaluation of locally isolated fungi through rapid screening for potential mycelium-based biofoam application in Malaysia - Nur Liyana, Mohd Izan; Ezyana, Kamal Bahrin; Hidayah, Ariffin; Mohd Zulkhairi, Mohd Yusoff; Norhayati, Ramli (Malaysian Society of Applied Biology, 2024)
Expanded polystyrene foam (EPS) contributes to environmental problems due to its inability to decompose in nature within a short period. In addition, petroleum as a core source for EPS is now depleting and new biological and environmentally friendly approaches are encouraged. As an alternative to EPS, mycelium-based biofoam (MBF) is a new foam technology formed of agricultural biomass and mycelium as a binding matrix is introduced. However, based on previous literature, the fungal strains used are mainly highlighted as one of the main factors which affect the final properties of MBF. Thus, this study aims to evaluate the most potential fungus used for MBF application using OPEFB, biomass from the palm oil industry as novel substrate using rapid screening. Twelve local fungi isolated from a local forest in Selangor, Malaysia were cultivated on Potato Dextrose Agar and OPEFB plate before being screened on agar containing four different types of dye indicators, which are methylene blue, guaiacol, Remazol Brilliant Blue R and azure B. As a result, Phanerochaete concrescens isolate LYN-UPM S1 and Perenniporia subtephropora isolate LYN-UPM S9 have shown the ability to produce ligninolytic enzymes and high content of chitin, which will be useful for the fabrication of mycelium-based biofoam.